Nanovectorized radiotherapy: a new strategy to induce anti-tumor immunity - Vanpouille-Box, Claire; Hindré, François (Frontiers in Oncology, 2012)
Recent experimental findings show that activation of the host immune system is required for the success of chemo- and radio-therapy. However, clinically-apparent tumors have already developed multiple mechanisms to escape anti-tumor immunity. The fact that tumors are able to induce a state of tolerance and immunosuppression is a major obstacle in immunotherapy. Hence, there is an overwhelming need to develop new strategies that overcome this state of immune tolerance and induce an anti-tumor immune response both at primary and metastatic sites. Nanovectorized radiotherapy that combines ionizing radiation and nano-devices, is one strategy that could boost the quality and magnitude of an immune response in a predictable and designable fashion. The potential benefits of this emerging treatment may be based on the unique combination of immuno-stimulatory properties of nanoparticles with the ability of ionizing radiation to induce immunogenic tumor cell death. In this review, we will discuss available data and propose that the nanovectorized radiotherapy could be a powerful new strategy to induce anti-tumor immunity required for positive patient outcome.